2009
DOI: 10.1038/clpt.2009.178
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors (VKORC1, CYP2C9, EPHX1, and CYP4F2) Are Predictor Variables for Warfarin Response in Very Elderly, Frail Inpatients

Abstract: Determining the optimal dose of warfarin for frail elderly patients is a challenging task because of the low dose requirements in such patients, the wide interindividual variability of response, and the associated risk of bleeding. The objective of this study was to address the influence of 13 common variations in eight genes on the maintenance dose of warfarin in a cohort of frail elderly inpatients. For our study, we enrolled 300 Caucasian subjects who were hospital inpatients, with a mean age of 86.7 +/- 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
7
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 45 publications
8
72
7
1
Order By: Relevance
“…among Turkish patients, with an assumption of the haplotype resemblance between Turks and Caucasians [24]. Although genotype frequency values were close to the study conducted among Caucasian patients, in contrast to the previous study, no significant relationship was observed between dose variations and allele types for Turkish patients.…”
Section: Discussioncontrasting
confidence: 44%
“…among Turkish patients, with an assumption of the haplotype resemblance between Turks and Caucasians [24]. Although genotype frequency values were close to the study conducted among Caucasian patients, in contrast to the previous study, no significant relationship was observed between dose variations and allele types for Turkish patients.…”
Section: Discussioncontrasting
confidence: 44%
“…28 In our study, the overall contribution of genetic factors (20.2%) to the interindividual variability in the warfarin maintenance dose was smaller than that reported in middle-aged adults (30%-40%) 6,7,9,10,12,13,[21][22][23] and similar to that found in the elderly (17.5%). 35 We did not find an association between warfarin maintenance dose and CYP4F2 genotype, probably because of the small size of the cohort. Interestingly, in our white pediatric cohort, the VKORC1 genotype had a far greater impact than the CYP2C9 genotype, in keeping with our results in very elderly patients.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, in our white pediatric cohort, the VKORC1 genotype had a far greater impact than the CYP2C9 genotype, in keeping with our results in very elderly patients. 35 These findings might reflect age-related changes in pharmacokinetics and/or liver function, affecting for example the expression or maturation of the liver enzymes VKOR and CYP, which affect the VKA pharmacodynamic target and VKA metabolism. 24,36 Takahashi et al studied Japanese children and adults to elucidate the developmental changes in the pharmacokinetics and pharmacodynamics of warfarin enantiomers with the goal of establishing pediatric dosage guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…22 Studies on European populations have indicated that CYP4F2 rs2108622 may account for an additional 1-7% of observed variation in warfarin dosing. 9,22,23 The effect of this CYP4F2 polymorphism seems to be substantially smaller than the effect of the VKORC1 and CYP2C9 variants, and the clinical relevance of CYP4F2 has recently been questioned. 24 The traditional approach for warfarin dosing is based on an initial fixed dose, followed by stabilization through trial and error.…”
Section: Introductionmentioning
confidence: 99%